Development of Rossi: Enhancing English Reading Skills by Using the Literacy Wheel Media - Oktadela, Resy; Shalawati, Shalawati; Hadiyanti, Putri Octa; Elida, Yusti; Nurrahmi, Nurrahmi (Universitas Pahlawan Tuanku Tambusai, 2024)
This research stems from the low reading proficiency observed among students during the the process of teaching English learning, which impacted various sectors, including primary education. The issue was especially prominent in English, a mandatory subject that needs to be mastered from an early age. Consequently, efforts were made to support students in learning English through the development of an interactive educational tool called